2016
DOI: 10.1016/j.bbalip.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced incorporation of dietary DHA into lymph phospholipids by altering its molecular carrier

Abstract: Several previous studies indicated that for optimal uptake by the brain, docosahexaenoic acid (DHA) should be present as phospholipid in the plasma. However most of dietary DHA is absorbed as triacylglycerol (TAG) because it is released as free fatty acid during digestion of either TAG-DHA (fish oil) or sn-2-DHA phospholipid (krill oil), and subsequently incorporated into TAG of chylomicrons. We tested the hypothesis that the absorption of DHA as phospholipid can be increased if it is present in the sn-1 posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 39 publications
0
35
0
4
Order By: Relevance
“…Moreover, lymph lipids were mainly composed of PL and TAG and the incorporation of EPA and DHA in lymph lipid fractions occurred independently of the molecular lipid species used (i.e. TAG, PL, lysophospholipids, NEFA) (23,(42)(43)(44) . Indeed, the FA profile of lymph TAG revealed similar n-3 PUFA levels between the three groups, suggesting that EPA and DHA were incorporated in lymph TAG regardless of the molecular FA carrier.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lymph lipids were mainly composed of PL and TAG and the incorporation of EPA and DHA in lymph lipid fractions occurred independently of the molecular lipid species used (i.e. TAG, PL, lysophospholipids, NEFA) (23,(42)(43)(44) . Indeed, the FA profile of lymph TAG revealed similar n-3 PUFA levels between the three groups, suggesting that EPA and DHA were incorporated in lymph TAG regardless of the molecular FA carrier.…”
Section: Discussionmentioning
confidence: 99%
“…The lipids were extracted from the fractions or tissues by the modified Bligh and Dyer procedure, as described by Ivanova et al (22), after adding tri-15:0 TAG and di-17:0 PC as internal standards. Methylation of FAs of total lipids and GC/MS analysis of the methyl esters was performed as described previously (20,23).…”
Section: Lipid Extraction and Fa Analysismentioning
confidence: 99%
“…Part of the LPC may also be hydrolyzed to free EPA, which is then incorporated into chylomicron TAG. Our previous studies on LPC-DHA showed that some of the PC formed from the absorbed LPC is transported in HDL particles secreted by the intestine (23). It is also possible that a part of dietary LPC is absorbed intact and transported in portal blood as LPC because of its hydrophilic property, although experimental evidence for this pathway is lacking.…”
mentioning
confidence: 99%
“…This is not a generalized phenomenon as LA levels were unchanged throughout the experimental period. This study adds to the current literature demonstrating increased systemic and tissue DHA levels through modification of the carrier system and/or fatty acid structure to facilitate absorption and optimize tissue incorporation [15]. …”
Section: Discussionmentioning
confidence: 92%